Association of human immunodeficiency syndrome with non-Hodgkin's lymphoma (Research, Society and Development, 2021)
HIV is the acquired immunodeficiency virus, characterized by viral replication and reduction of CD4 + T lymphocytes. It is part of the genus Lentivirus and the Retroviral family. In addition, it can also cause immunological changes and opportunistic infections, leading to the development of acquired immunodeficiency syndrome (AIDS), which is the advanced clinical manifestation of the virus. Non-Hodgkin's lymphoma is considered the second most common cancer among AIDS patients. The work aims to expose the main causes of the association of Acquired Immunodeficiency Syndrome with Non-Hodgkin's Lymphoma. This is a qualitative bibliographic review that is based on scientific production based on studies that have already been published. Since the first description of the Acquired Immunodeficiency Syndrome, its association with the increased risk of forming multiple tumors has become clear. The very definition of AIDS, in addition to the relationship with various opportunistic infections, also includes certain types of tumors, such as (non-Hodgkin's lymphoma, Kaposi's sarcoma and cervical cancer). One of the most common cancers associated with AIDS is non-Hodgkin's lymphoma, a neoplasm that affects the lymphatic system of patients and that has a poor prognosis and a low life expectancy for these patients. It is quite common for AIDS patients with nonspecific clinical manifestations not to undergo treatment and only discover the infection during treatment for lymphomas.